2015
DOI: 10.1007/s00590-015-1604-7
|View full text |Cite
|
Sign up to set email alerts
|

External fixation using locking plate in distal tibial fracture: a finite element analysis

Abstract: To guarantee a stable external plate fixation in distal tibial fracture, the plate-bone distance should be less than 30 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 18 publications
3
33
0
Order By: Relevance
“…The differences of samples in LCP group and EF-tibia group were the distance between the bone and the plate, with other factors keeping consistent. The results of the comparison are consistent with previous report that the stiffness decreases with the increase of the bone-plate distance [12], and the distance used in this study, i.e., 30 mm, is the upper bound to keep external platefixation stable in a distal tibia fracture [13]. The bone-plate distances in EF-tibia and EF-femur groups were the same; while the medial distal femur plate had different diameters of the screws and dimensions of the plate from the medial distal tibial plate.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The differences of samples in LCP group and EF-tibia group were the distance between the bone and the plate, with other factors keeping consistent. The results of the comparison are consistent with previous report that the stiffness decreases with the increase of the bone-plate distance [12], and the distance used in this study, i.e., 30 mm, is the upper bound to keep external platefixation stable in a distal tibia fracture [13]. The bone-plate distances in EF-tibia and EF-femur groups were the same; while the medial distal femur plate had different diameters of the screws and dimensions of the plate from the medial distal tibial plate.…”
Section: Discussionsupporting
confidence: 91%
“…Ma et al and Zhang et al investigated the finite element analysis model, but didn’t make a comparison of stiffness between external plating and conventional LCP [9, 13]. Kanchanomai et al and Ahmad et al reported a tibial shaft fracture model, instead of a distal tibial fracture model [12, 14].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 12 studies [ 3 , 14 – 21 , 23 25 ] were included in this systematic review. These consist of 3 pure biomechanical studies, [ 23 25 ] 8 case series, [ 3 , 14 , 16 21 ] and 1 study including both of biomechanics and case series. [ 15 ] The overall population included 254 patients (112 cases of closed fractures), with 167 males and 87 females.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmad M et al in their study found that strength and construct stability significantly reduces when plate bone distance is more than 2 mm [19]. Zhang J, Ebrahim N in their study concluded that for stable external fixation with LCP, the plate bone distance should be less than 30mm [20]. Wei Lu, Li Hui in their study of comparison of axial and torsional stiffness of LCP found femoral LCP to be significantly better than tibial LCP [21].…”
Section: Original Research Articlementioning
confidence: 95%